Efikasi Diri Anak Usia 6-18 Tahun yang Mengalami Thalasemia: Self-efficacy of children aged 6-18 years with thalassemia - Stella Pramasita Arundina; Lina Dewi Anggraeni; Paramitha Wirdani Ningsih Marlina (Fakultas Keperawatan Universitas Andalas, 2020)
Thalassemia patient should undergo a repeated treatment, so it causes side effects on his health both physically and psychologically.The most common psychological problem suffered by the patient is the decreasing of self efficacy which affects the attitude and mindset of children with thalassemia.The purpose of this research is to find out the 6-18 years old children self efficacy portrayal with thalassemia on hospital X, West Jakarta. The research design used in this research was quantitative descriptive and cross sectional approach and questionnaire with interview as the instruments. The sampling technique used is total sampling with the number of sample of 50 children, conducted on January 2019. The data analyses used were shapiro wilk normality test and frequency distribution test. The result showed that 62% including 6-12 years with 60% female sex, respondents who underwent therapy <10 years as much as 52% with early age diagnosed at <1 year as much as 38%. Self efficacy was high in the 13-18 year age group as much as 63.2%, self-efficacy on the general aspects in the 6-12 year age group (58.1%) and 13 18 years old (57.9%) were categorized good, self efficacy on the aspects of strength in the 6-12 year age group (74,2%) and 13-18 year old (73,7%) were categorized good and a high selfefficacy on the aspect of level in the 13-18 year age group as much as 63,2%.It is recommended that children with thalassemia can control their self efficacy every day as an effort to maintain their health.